PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN ( Studi Pada Penumpang Bus PO. Shantika Jurusan Jepara - Jakarta ) - Febrian Rangga Saputra, 08.05.51.0021; Irsad, Moch. (Students Journal of Economic and Management, 2012)
Inthe era of competition in the business world that is increasingly tight, demanding business people should be able to maximize the performance of the company in order to compete in the marketplace. One of them is to improve the quality of service and pricing to achieve customer satisfaction. The better the quality of service and price is given it will increase customer satisfaction. The study, entitled "EFFECT ON PRICE AND QUALITY SERVICE CUSTOMER SATISFACTION PO PASSENGER BUS. MAJOR SHANTIKA JEPARA - JAKARTA "aims to analyze the influence of service quality and customer satisfaction rates of PO bus passengers. Shantika majoring in Jepara - Jakarta. Samples used in this study of 100 respondents with a sampling technique is Puposive Sampling is a technique of determining if the information for the data samples taken from specific targets, by taking a sample with specific criteria (Sugiyono, 2007). The criterion is an adult (minimum age 17 years) and have been using the bus service PO. Shantika least 3 times. The data used are the primary data and secondary data analysis using qualitative and quantitative analyzes covering validity, reliability testing, multiple linear analysis, determination coefficient and hypothesis test that includes a t test and F test Based on data analysis and test the hypothesis that the partial results obtained in the variable quality of service has a positive and significant impact on customer satisfaction. The most influential variables are dominant to the satisfaction of consumers of the variable quality of service and price are the quality of service that is equal to 78.1% and rates of only 13.7%.Key words: Quality of service, price, and customer satisfaction